N Glycolylation of the Nucleotide Precursors of Peptidoglycan Biosynthesis of Mycobacterium spp. Is Altered by Drug Treatment - Mahapatra, Sebabrata (American Society for Microbiology, 2005)
The peptidoglycan of Mycobacterium spp. reportedly has some unique features, including the occurrence of N-glycolylmuramic rather than N-acetylmuramic acid. However, very little is known of the actual biosynthesis of mycobacterial peptidoglycan, including the extent and origin of N glycolylation. In the present work, we have isolated and analyzed muramic acid residues located in peptidoglycan and UDP-linked precursors of peptidoglycan from Mycobacterium tuberculosis and Mycobacterium smegmatis. The muramic acid residues isolated from the mature peptidoglycan of both species were shown to be a mixture of the N-acetyl and N-glycolyl derivatives, not solely the N-glycolylated product as generally reported. The isolated UDP-linked N-acylmuramyl-pentapeptide precursor molecules also contain a mixture of N-acetyl and N-glycolyl muramyl residues in apparent contrast to previous observations in which the precursors isolated after treatment with d-cycloserine consisted entirely of N-glycolyl muropeptides. However, nucleotide-linked peptidoglycan precursors isolated from M. tuberculosis treated with d-cycloserine contained only N-glycolylmuramyl-tripeptide precursors, whereas those from similarly treated M. smegmatis consisted of a mixture of N-glycolylated and N-acetylated residues. The full pentapeptide intermediate, isolated following vancomycin treatment of M. smegmatis, consisted of the N-glycolyl derivative only, whereas the corresponding M. tuberculosis intermediate was a mixture of both the N-glycolyl and N-acetyl products. Thus, treatment with vancomycin and d-cylcoserine not only caused an accumulation of nucleotide-linked intermediate compounds but also altered their glycolylation status, possibly by altering the normal equilibrium maintained by de novo biosynthesis and peptidoglycan recycling.